Tukey HSD Post Hoc Test untuk Perbandingan Karakteristik Lingkungan dan Sumber Daya Provinsi-Provinsi di Indonesia : Tukey HSD Post Hoc Test for Comparison of Environment Characteristic and Resources of Provinces in Indonesia - Bunga Mardhotillah; Syamsyida Rozi; Zuli Rodhiyah (Universitas Jambi, 2021)
Environmental Characteristics has several components, including the quality of the Environment and Environmental Resources which consist of mineral resources, energy resources, land, land resources, biological resources, and water resources. The provinces in Java, Sumatra, Kalimantan, dan Sulawesi still rely on natural resources for their economic growth. Environmental Quality can be measured by various indices, some of which are the Air Quality Index and the Water Quality Index. One of the problems in the National Economic Recovery during the Covid-19 Pandemic Period is the unavailability of studies and research related to similarities and differences in environmental characteristics to identify provinces that have the potential to prioritize the distribution of Funds/Budgets from the Central Government. Knowing the Similarities and Differences in Characteristics is also needed in determining the Destination Areas for comparative studies from one province to another. For this reason, it is necessary to recommend environmental sector policies as material for the preparation of regulations and the use of appropriate technology in overcoming environmental problems. Analysis of Variance Comparison of Environmental Characteristics and Resources of the Provinces on the four Big Islands in Indonesia shows a significant F - Statistics value, so a Tukey HSD Post Hoc Test is needed to recommend Priority Provinces based on similarities and differences in characteristics in the context of Strengthening the Environmental Sector, as well as recommendations for similarities between regions as a material for consideration for comparative studies between Regional / Provincial Governments.